2013
DOI: 10.7556/jaoa.2013.007
|View full text |Cite
|
Sign up to set email alerts
|

A Research Primer: Basic Guidelines for the Novice Researcher

Abstract: Research can achieve many objectives, primarily by establishing a supportable, verifiable basis for clinical decisions. An evidence-based practice can streamline patient care, improving safety through consistency of care and making health care more affordable for patients. By cultivating research skills, osteopathic physicians and trainees can begin to forge a reciprocal relationship with medical literature and current findings, approaching research as active contributors as well as consumers. Many challenges,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…3,9,13,21 Conclusions were that many SAPNs may be less familiar with the value of replicating published project articles, possibly due to pressure towards producing SA projects from more "established" (i.e., more readily recognizable) types of studies, e.g., randomized clinical trials (RCTs), etc. 25,26,[29][30][31] • "My project must be an entirely new design. "…”
Section: Initial Project Designmentioning
confidence: 99%
See 4 more Smart Citations
“…3,9,13,21 Conclusions were that many SAPNs may be less familiar with the value of replicating published project articles, possibly due to pressure towards producing SA projects from more "established" (i.e., more readily recognizable) types of studies, e.g., randomized clinical trials (RCTs), etc. 25,26,[29][30][31] • "My project must be an entirely new design. "…”
Section: Initial Project Designmentioning
confidence: 99%
“…9,10,32 For example, the authors have heard from the SAPN, "I thought it would be interesting to study individuals with condition x." Although this type of orientation may eventually lead to useful descriptive pilot (i.e., more exploratory, descriptive) projects, 5,31,33 the authors have generally concluded that this may comprise an unrealistic desire to study especially terribly complex healthcare topics in initial projects.…”
Section: Spartan Medical Research Journalmentioning
confidence: 99%
See 3 more Smart Citations